Hyperacusis among adults with occupational noise exposure - Mat Nasir, Nurul Lydia Nazifa; Tengku Zam Zam, Tengku Zulaila Hasma; Ismail, Noraidah (IIUM Press, 2025)
Introduction: Hyperacusis is an increased sensitivity and reduced tolerance to sounds at an acceptable level for most people. This research effort addresses this critical gap in understanding the role of occupational workers as one of the contributing factors of hyperacusis and Modified Hyperacusis Questionnaire as a valuable tool for early identification of hyperacusis in the adult population. Objectives: This study aimed to study the existence of hyperacusis among adults who are exposed to occupational noise. Methodology: A cross-sectional study was conducted using convenience sampling technique. A total of 95 workers in Malaysia participated. Data were collected using the Modified Khalfa Hyperacusis Questionnaire, which was developed by Khalfa, 2002. Results: Most workers (57.9%) are not well informed regarding the existence of hyperacusis. More than half of the participants who were exposed to noise in the working environment were reported to have hyperacusis. Only 4% of the participants were reported to have normal sound tolerance. Furthermore, a Mann-Whitney U test showed no significant difference in awareness of hyperacusis between adults with occupational noise exposure and without occupational noise exposure (p=0.62). Conclusion: the findings highlight a considerable gap in workers awareness regarding hyperacusis. This underscores the need for education and occupational safety regulations to enhance workers’ awareness and management of noise in the work environment to create conducive working spaces for them